Polarization Study of Pc1 and Pc1-2 Band Pulsations at Conjugate Stations - Ishizu, Mitsuo; Saka, Ousuke; Kitamura, Tai-Ichi; Fukunishi, Hiroshi; Sato, Natsuo; Fujii, Ryoich (1981)
P(論文) Polarization analyses were made on Pc1 and unstructured Pc 1-2 band pulsations observed at a conjugate pair, Husafell, Iceland and Syowa Station, Antarctica, in August and September 1977. It was found that L mode is predominant at Syowa Station, while R mode is at Husafell. From the comparison with the polarization at these stations, it was concluded that these two stations would not be in the conjugate relation in a strict sense at this time. departmental bulletin paper